Acute Blood Loss: Regional Blood Flow and Microcirculation (Review, Part II) - V. V. Moroz; I. A. Ryzhkov (Общая реаниматология)
It was shown in the first part of the review that the alterations of systemic hemodynamics and microcirculation in acute blood loss led to the development of metabolic disorders and cell damage. The second part of the review highlights the methods of microcirculation and tissue oxygenation investigation. The focus is on modern biomicroscopy varieties and methods based on the laser technology. In particular, we discuss a method based on the mathematical analysis of microvascular blood flow oscillations (fluxmotion) to evaluate the regulatory mechanisms of microcirculation. The features of regional blood flow and microcirculation in different vascular regions of the body in acute blood loss, as well as during the subsequent reperfusion are considered. It was shown that microcirculatory alterations in a particular organ are largely determined by the structural and functional features of its blood supply, as well as by the role of this organ in the pathogenesis of acute blood loss. These changes can possess both adaptive and pathological significance depending on blood loss stage and severity.